Issues Of The Land Office In Determining Land Rights On Duplicate Certificates - Ivana Wulandari; Sentot Sudarwanto, Albertus; Purwadi, Hari (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
Land is one of the fundamental sources of human life, ensuring human survival. Every individual who owns land requires proof of ownership, namely a land certificate, which is issued by the Land Office. Certificates can be issued upon land registration with the aim of providing protection and legal certainty to land rights holders. However, it is not uncommon for issues to arise with some land certificates, leading to legal disputes, such as Duplicate Certificates. The purpose of this research is to identify, analyze, and examine the issues in determining land rights holders in cases of Duplicate Certificates. This research employs an empirical legal research approach, conducted at the Land Office of the ATR/BPN in Klaten Regency. It is supported by literature review to obtain necessary data such as theories, doctrines, principles, and other legal provisions. Secondary legal sources used include textbooks, legal dictionaries, legal journals, and commentaries on court decisions, which are relevant to primary legal sources and aid in the analysis of this research. The findings of this research indicate that the issue arises when disputing parties fail to reach an agreement through mediation, leading to legal proceedings in court and ultimately, a binding legal decision.